PENGARUH KEPRIBADIAN DAN DUKUNGAN ORGANISASI TERHADAP PROFESIONALISME, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN KINERJA - Noviana Tursanurohmad (Jurnal Litbang Polri, 2019)
This study aims to examine a theoretical model that describes the influence between Personality, organizational support influence on professionalism, Organizational Citizenship Behavior (OCB) and performance at the Makassar Polrestabes in Makassar City. Data collection using questionnaires, sampling techniques using simple random sampling which is adjusted to the proportion of each function. The number of samples is 299 respondents. Data was analyzed by using Warp PLS. The results of the study prove that (1) Personality has a significant positive effect on professionalism. (2). organizational support has a significant positive effect on professionalism. (3) Personality has a significant positive effect on Organizational Citizenship Behavior (OCB). (4) organizational support has a positive and insignificant effect on Organizational Citizenship Behavior (OCB). But organizational support has an indirect effect on Organizational Citizenship Behavior through professionalism (5) professionalism has a significant positive effect on Organizational Citizenship Behavior (OCB). (6) Personality has no significant positive effect on performance. But Personality has an indirect effect on performance through professionalism and Organizational Citizenship Behavior (OCB). (7) organizational support has no significant positive effect on performance. But organizational support has an indirect effect on performance through professionalism and Organizational Citizenship Behavior (OCB). (8) professionalism has a significant positive effect on performance. (9) Organizational Citizenship Behavior (OCB) has a significant positive effect on performance.